Clinical and Molecular Analysis of Pathologic Fracture-associated Osteosarcoma: MicroRNA profile Is Different and Correlates with Prognosis. Issue 9 (September 2019) - Lozano Calderón, Santiago A.; Garbutt, Cassandra; Kim, Jason; Lietz, Christopher E.; Chen, Yen-Lin; Bernstein, Karen; Chebib, Ivan; Nielsen, G. Petur; Deshpande, Vikram; Rubio, Renee; Wang, Yaoyu E.; Quackenbush, John; et al.
Abstract: Background: MicroRNAs are small, noncoding RNAs that regulate the expression of posttranslational genes. The presence of some specific microRNAs has been associated with increased risk of both local recurrence and metastasis and worse survival in patients with osteosarcoma. Pathologic fractures in osteosarcoma are considered to be more the manifestation of a neoplasm with a more aggressive biological behavior than the cause itself of worse prognosis. However, this has not been proved at the biological or molecular level. Currently, there has not been a microRNA profiling study of patients who have osteosarcoma with and without pathologic fractures that has described differences in terms of microRNA profiling between these two groups and their correlation with biologic behavior. Questions/purposes: (1) In patients with osteosarcoma of the extremities, how do the microRNA profiles of those with and without pathologic fractures compare? (2) What relationship do microRNAs have with local recurrence, risk of metastasis, disease-specific survival, and overall survival in osteosarcoma patients with pathologic fractures? Methods: Between 1994 and 2013, 217 patients were diagnosed and treated at our institution for osteosarcoma of the extremities. Patients were excluded if (1) they underwent oncologic resection of the osteosarcoma at an outside institution (two patients) or (2) they were diagnosed with an extraskeletal osteosarcoma (29 patients) or (3) they had less than 1 year of clinical follow-up and no oncologic outcome (local recurrence, metastasis, or death) (four patients). A total of 182 patients were eligible. Of those, 143 were high-grade osteosarcomas. After evaluation of tumor samples before chemotherapy treatment, a total of 80 consecutive samples were selected for sequencing. Demographic and clinical comparison between the sequenced and non-sequenced patients did not demonstrate any differences, confirming that both groups were comparable. Diagnostic samples from the extremities of 80 patients with high-grade extremity osteosarcomas who had not yet received chemotherapy underwent microRNA sequencing for an ongoing large-scale osteosarcoma genome profiling project at our institution. Six samples were removed after a second look by a musculoskeletal pathologist who verified cellularity and quality of samples to be sequenced, leaving a total of 74 patients. Of these, two samples were removed as they were confirmed to be pelvic tumors in a second check after sequencing. The final study sample was 72 patients (11 patients with pathologic fractures and 61 without). Sequencing data were correlated with fractures and local recurrence, risk of metastasis, disease-specific survival, and overall survival through Kaplan-Meier analyses. Results: Several microRNAs were expressed differently between the two groups. Among the markers with the highest differential expression (edgeR and DESeq algorithms), Hsa-mIR 656-3p, hsa-miR 493-5p, and hsa-miR 381-3p were upregulated in patients with pathologic fractures, whereas hsa-miR 363, hsa-miR 885-5p, and has-miR 20b-5p were downregulated. The highest differential expression fracture and nonfracture-associated microRNA markers also distinguished groups of patients with different metastasis risk, a well as different disease-specific and overall survival. Furthermore, the profile of pathologic fractures demonstrated a higher differential expression for microRNA markers that were previously associated with a higher risk of metastasis and lower survival rates in patients with osteosarcoma. Conclusions: In patients who have osteosarcoma, the microRNA profiles of those with pathologic fractures are different than of patients without pathologic fractures. The highest differential expression mircroRNA molecules in patients with pathologic fractures predict also higher risk of metastatic disease as well as worse disease-specific survival and overall survival. Furthermore, we found higher differential expression of microRNAs in the pathologic fracture group previously associated with poor prognosis. The higher risk of metastasis and poorer overall survival in patients with pathologic fractures is inherent to tumor aggressive biologic behavior. It is plausible that the fracture itself is not the direct cause of worse prognosis but another manifestation of tumor biologic aggressiveness. Identification of these molecules through liquid biopsies may help to determine which patients may benefit from surgery before fractures occur. The same technology can be applied to identify patterns of response to conventional chemotherapy, assisting in more specific and accurate systemic therapy. Level of Evidence Level: III, prognostic study.